Can Religion Overcome Violence? A Mimetic Perspective - Antonysamy, Morris (Jnanadeepa, 2017)
The intimate relationship between religion and violence has been a perennial question in the realm of social harmony and peace. Many approaches have been attempted to explain this enigmatic link. However, this linkage is still exploratory and brings forth ever new challenges. This paper approaches this relationship from the viewpoint of mimetic theory of Rene Girard. From an anthropological perspective, mimetic theory tries to explore the roots of violence in the evolution of cultures. It takes us to the deeper question o f how we define and understand religion. From a universal theorization we look at the Indian scenario which offers quite many insights as well as certain challenges. Indian history, just like the world history, revolves around the mimetic fabric of conflict and violence. In the light of this discussion, the author proposes certain means of overcoming mimetic conflicts and violence. Eventually it tries to address the question of divergence between religion and politics.